Respon Pembungaan Tanaman Melon (Cucumis Melo L.) Terhadap Aplikasi Berbagai Dosis Pupuk MKP dan POC Asam Amino - Fadilla Eka Rohcahyani; Ratna Mustika Wardhani (Universitas Merdeka Madiun, 2025)
Melons are a horticultural commodity with high economic value and are popular among consumers. Efforts to improve melon cultivation to increase production and fruit quality are necessary. The flowering phase in melon cultivation is a critical phase that greatly affects the success of the melon harvest. The combination of MKP fertilizer, which is an inorganic fertilizer, and amino acid LOF (Liquid Organic Fertilizer), which is an organic fertilizer, is expected to improve the flowering phase of melon plants. This study aims to determine the appropriate combination of MKP fertilizer and amino acid LOF doses to improve flowering in melon plants. The study was conducted from April 2024 to July 2024. The research was conducted on farmers' land in Jatirejo Village, Nganjuk District, Nganjuk Regency. This study used a factorial experiment arranged in a Randomized Block Design (RBD) consisting of 2 factors. Factor I was the MKP fertilizer dose, consisting of 3 levels, namely M1 (5 g/plant), M2 (10 g/plant), M3 (15 g/plant), and factor II was the amino acid LOF dose consisting of 4 levels, namely A0 (control), A1 (50 ml/plant), A2 (100 ml/plant), A3 (150 ml/plant). The parameters used were the age of the first flower, the number of female flowers, the number of male flowers, and the total number of flowers. Data analysis was performed using ANOVA and a 5% significance level. The combination of 15 g/plant of MKP fertilizer and 100 ml/plant of amino acid LOF was the best treatment combination for increasing the number of male flowers and the total number of flowers on melon plants.